Development of Lectora Inspire as Interactive Multimedia Chemistry Learning in Senior High School - Roza Linda; Erviyenni Erviyenni; Asmadi M. Noer; NurAzlina Oktavianti; Novia Sellyna (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract: Research development of LectoraInspire Interactive Multimediafor Salt Hydrolysisand Rate of Reactiontopics aims to getavalidand practical learning media. The researchmethodwas ResearchandDevelopment withPlompmodel in LectoraInspire Interactive Multimediafor Salt Hydrolysistopic and Four-D model forReaction Ratetopic. Both Media werevalidated bythree validators andthelimitedtrialbypractitioners (users).The results showed an average score of 96.05% validator ratings for Lectora Inspire interactive multimedia on the topic of salt hydrolysis and 95.63% for interactive multimedia on the topic of reaction rate.The data analysis is based on questionnaire responses of teachers and students each earned an average score of 96.67% and 97.3% for Lectora Inspire on the topic reaction rate, 98.3% and 96.5% for Lectora Inspire on the topic Hydrolysis Salt. From the results of the average overall score of validation and testing of media-based learning Lectora Inspire on the topic of reaction rate and hydrolysis Salt were valid and can be used as a learning media.Keywords:interactivemultimedia, lectorainspire, salthydrolysis, rate reaction